Formulation and in-vitro Evaluation of Carvedilol Gastroretentive Capsule as (Superporous Hydrogel) - Jihad, Haider Mohammed; J. Al- Akkam, Entidhar (Iraqi Journal of Pharmaceutical Sciences, 2021)
The preferred route of drug administration is the oral route, but drugs with narrow absorption window in the gastrointestinal tract are still challenging. The ability to extend and monitor the gastric emptying time is a valuable tool for processes remaining in the stomach longer than other traditional dosage forms.The purpose of this study was to formulate and evaluate gastroretentive superporous hydrogel (SPH) of carvedilol with view to improve its solubility and increase gastric residence time in order to get sustained release formulas via utilization of various kinds and concentrations of hydrophilic polymers then after, incorporate the best prepared formula into capsules. Sixteenth formulae of SPH hybrid were prepared by gas blowing technique from the following materials; monomers (Poly vinyl alcohol, and Acrylamide), cross-linkers (Methylene bisacrylamide, and glutaraldehyde), hybrid agent (Chitosan), foaming agent (NaHCO3) and foam stabilizer (Tween 80). Different amounts or concentrations of these materials were utilized to investigate their effect on SPH properties (density, porosity, floating, drug content, drug release, swelling time, and swelling ratio). The soaking procedure was utilized for loading of carvedilol into SPH hybrid (6.25mg/2.5g SPH). After analysis the results statistically and application the similarity factor (f2) equation, formula F8 was selected as the best formula and incorporated into capsules. The drug release data were applied to different mathematical kinetics and the results were shown to be fitted to Higuchi model and the release mechanism was (non fickian) diffusion.The overall results suggested that the proposed SPH hybrid drug delivery system is encouraging for carvedilol specific delivery to the stomach.